2015
DOI: 10.1097/j.pain.0000000000000256
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-induced pain sensitization in men and women

Abstract: Endotoxin-induced systemic immune activation leads to visceral and musculoskeletal hyperalgesia in healthy humans, irrespective of biological sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 65 publications
4
49
0
2
Order By: Relevance
“…23,25 All of these studies, however, also provided negative findings with respect to sex differences in visceral sensitivity, in line with our present data from a large sample of healthy men and women and earlier work assessing visceral pain modulation during placebo analgesia 26 or an immune challenge. 22 Our findings from regression analyses confirmed that, at least in young healthy participants, sex was no predictor of visceral sensitivity. Furthermore, GI symptoms, chronic stress load, or trait anxiety as factors reportedly contributing to altered visceral sensitivity in patients with chronic visceral pain conditions 8,9 could not explain interindividual variability in visceral sensitivity.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…23,25 All of these studies, however, also provided negative findings with respect to sex differences in visceral sensitivity, in line with our present data from a large sample of healthy men and women and earlier work assessing visceral pain modulation during placebo analgesia 26 or an immune challenge. 22 Our findings from regression analyses confirmed that, at least in young healthy participants, sex was no predictor of visceral sensitivity. Furthermore, GI symptoms, chronic stress load, or trait anxiety as factors reportedly contributing to altered visceral sensitivity in patients with chronic visceral pain conditions 8,9 could not explain interindividual variability in visceral sensitivity.…”
Section: Discussionsupporting
confidence: 78%
“…To date, however, existing evidence of sex differences in healthy visceral sensitivity, as assessed using experimental models of esophageal or rectal distensions, is inconclusive, [14][15][16] with several studies failing to demonstrate differences in visceral sensitivity between healthy men and women. 6,[17][18][19][20][21][22][23][24][25][26] Inconsistent and partly contradicting findings in previous work might at least in part be due to small sample sizes insufficient for the detection of subtle differences in visceral sensitivity. Furthermore, IBS-related factors such as stress, anxiety, or subclinical gastrointestinal (GI) symptoms, which could contribute to changes in visceral sensitivity in a sex-specific manner, have not been systematically considered.…”
mentioning
confidence: 99%
“…Data were pooled from four previously published randomized, placebo-controlled studies. 15,31,43,44 To exclude that the primary outcome (i.e., symptom reporting) was affected by a previous experience with LPS treatment, all subjects included were na€ ıve to LPS. In addition, data from crossover studies were only included from the first of two consecutive study days.…”
Section: Participantsmentioning
confidence: 99%
“…In general, females produce stronger cellular and humoral immune reaction in gut-associated lymphoid tissue and blood, 162,163 are more likely to develop autoimmune diseases compared to men, 164 and have higher inflammatory response to low-dose lipopolysaccharide administration, although these seems not to increase pain sensitivity compared to males. 165 Estrogens may promote both pro-and anti-inflammatory pathways depending on the estrogen level, the cell type and tissue studied, specific inflammatory factors, the time course of the inflammatory response (e.g., acute vs chronic), and the time point at which estrogen exposure occurs. 164 In addition, ERb-knockout mice have revealed that ERb plays a pivotal role in the organization and architectural maintenance of the colon.…”
Section: Immune Systemmentioning
confidence: 99%